2015
DOI: 10.1186/s40623-015-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of ionospheric mid-latitude trough over the Northern Hemisphere derived from GPS total electron content data

Abstract: This study statistically investigated the seasonal variation, magnetic local time (MLT) variation, geomagnetic activity dependence, and solar activity dependence of the mid-latitude trough using GPS total electron content (TEC) data from 2000 to 2014. The daily median Kp index was used to characterize the daily geomagnetic activity level. The results showed that the trough minimum position depended primarily on the geomagnetic activity, MLT, and the season. The trough depth depended primarily on the solar flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 29 publications
9
41
0
Order By: Relevance
“…The corresponding time intervals for NIMS were 21:00 to almost 23:00, 23:00 to almost 01:00, and 01:00 to almost 03:00 UT. tical study of Yang et al (2015) shows a consistent decrease in magnetic latitude from low to high Kp values. In such comparisons, it is important to appreciate that different observing techniques have been used and during different times in the solar cycle.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The corresponding time intervals for NIMS were 21:00 to almost 23:00, 23:00 to almost 01:00, and 01:00 to almost 03:00 UT. tical study of Yang et al (2015) shows a consistent decrease in magnetic latitude from low to high Kp values. In such comparisons, it is important to appreciate that different observing techniques have been used and during different times in the solar cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Lunt et al (1999) observed an average TEC difference between NIMS and GPS of some 1.6 TECU at 50.4 • N, reducing to 0.75 TECU at 51.4 • N and to about 0.05 TECU at 52.4 • N at solar minimum. Yang et al (2015) also report an essentially constant TEC at the trough minimum of about 4-5 TECU regardless of Kp, and indicate that investigation of the TEC and temperature at the trough minimum is needed to help with understanding the physical processes responsible for trough formation. When they categorized the data by season, a small decrease in TEC was observed at the trough minimum with MLT at summer and equinox.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trough is discovered as early as 1960s by using topside sounder (Muldrew, ). Following that, scientists using ground‐based ionosonde networks (Dudeney et al, ; Rodger & Pinnock, ; Rothkaehl et al, ; Whalen, ), incoherent scatter radar facilities (Hedin et al, ; Ishida et al, ; Weber et al, ), and Global Positioning System (GPS) TEC (total electron content) measurements (Krankowski et al, ; Le et al, ; Yang et al, ; Yizengaw & Moldwin, ) observed the trough. Nevertheless, these observations confirm that the trough is a nighttime prominent phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The latitudinal range between 40° and 70° magnetic latitude has been demonstrated to be suitable by Yang et al (2015). Deminov et al (1995a) demonstrated that the trough position primarily depends on the actual magnetic activity level.…”
Section: Selection Of Trough-like Phenomenamentioning
confidence: 99%